Effect of surface overlayer in enhancing the photoelectrochemical water oxidation of in situ grown one-dimensional spinel zinc ferrite nanorods directly onto the substrate. Issue 74 (30th August 2018) - Sahu, Tushar Kanta; Shah, Adit Kumar; Gogoi, Gaurangi; Patra, Anindya Sundar; Ansari, Mohammad Shaad; Qureshi, Mohammad
Abstract : Overlayer passivation minimizes surface defects and arrests the back transfer of electrons for an enhanced charge extraction. Abstract : Overlayer passivation minimizes surface defects and arrests the back transfer of electrons for an enhanced charge extraction. Surface passivation of ZnFe2 O4 using alumina yields enhanced charge carrier density from 8.43 × 10 20 cm −3 to 18.83 × 10 20 cm −3 giving a record efficiency in this class of compounds.